Indoor Positioning for Multiphotodiode Device Using Visible-Light Communications - Wei Xu; Jia Wang; Hong Shen; Hua Zhang; Xiaohu You (IEEE Photonics Journal)
With the widespread use of light-emitting diodes (LEDs) for lighting, their ability to support communications through visible light has become promising for various wireless applications. In particular, visible-light communication (VLC) assisted indoor positioning enjoys its unique advantage of electromagnetic interference immunity and high accuracy. Instead of directly extending conventional wireless positioning using radio-frequency equipment, we consider the indoor positioning specified for a popular VLC scenario where the target device has multiple photodiodes (PDs) while having no help from other fixed receiving nodes with known coordinates. A general framework is presented for multi-PD device positioning by exploiting relative positions, as well as the received signal strength indications, of the multiple PDs. Moreover, the feasible condition for realizing effective positioning is also presented. Finally, we validate the accuracy of the proposed method via numerical tests.